The following should help you work towards the answer.

1. Let us first put all of the constant terms together. The constants are the numbers without a variable. In this equation they are the -12 and 83.

Let us add 12 to the left side of the equation, since -12+12 will equal 0. Of course if we add 12 to the left side, we also need to add 12 to the right side.

3x-12=-2x+83

+12= +12

3x+0=-2x+95

Now the equation is: 3x=-2x+95

2. Let us now put the x values together. Above we added 12 since we knew -12+12=0. For the x values I am going to add 2x to the right side, since -2x+2x=0. Of course if we add 2x to the right side, we have to also add 2x to the left side.

3x=-2x+95

+2x=+2x

5x=0x+95

Now the equation is: 5x=95

3. Let us "undo" the 5 times x. The equation 5x=95 is a simple way of saying x+x+x+x+x=95, which means that 5 x's will make 95. If I want each x to have an equal piece of 95, then I will have to divide 95 into 5 equal parts. Therefore I will divide 95 by 5.

5x=95

5 = 5

x=19

4. Check!!! Go back and plug 19 in for the x value and make sure it works.

3(19)-12=-2(19)+83

45=45